John Stucky correspondence - Stucky, John.
ALS written by Stucky aboard the ship Montezuma off the coast of Antigua to John Clapp, Philadelphia, Pa., describing U.S. naval actions against French privateers in the Caribbean.
Seaman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Clapp, John, -- active 1798 -- Correspondence; Montezuma (Ship); United States. -- Navy -- Foreign service -- Antigua and Barbuda -- Antigua; United States. -- Navy -- History; Privateering -- Caribbean Sea; France -- History, Naval -- 18th century; Seamen